Um modelo de arquitetura de sistema de e-voting auditável utilizando blockchain - Bezerra, Wagner Luiz Braga (2023)
The emergence of blockchain technology, initially with the cryptocurrency Bitcoin, has brought with it a range of possibilities for developing solutions in the most diverse sectors of society. The characteristics of the technology guarantee various advantages such as immutability, irrefutability, auditability and transparency. In addition, because the information is replicated in all nodes of the network, blockchain provides decentralization, disintermediation and availability. The blockchain platform Hyperledger platform, offers frameworks such as Fabric, which are designed to meet business needs with private and permissible networks, guaranteeing control and privacy. This decentralized and distributed system has found significant applicability in the realm of e-voting, offering solutions to crucial issues such as the integrity, authentication and security of votes. This record is accessible to all network participants, guaranteeing the traceability and verifiability of election results. The immutability of the data in the blockchain ensures that no information is altered or tampered with, increasing confidence in the electoral process. Auditing is a recognized management technique that provides an overview of the situation regarding specific resources and services within an organization. In the corporate environment there are various types of audits, including information systems audits, so there is no definite consensus in the literature on a single audit methodology. This paper develops a study on the use of blockchain technology in e-voting systems with the inclusion of simplified auditing processes and low or no implementation costs. A state-of-the-art search is carried out in order to gain an insight into scientific production on the subject. Experiments are carried out with the Hyperledger platform. An application is created to test the functioning of the proposed architecture. At the end of the development process, it is possible to conclude that the work meets what was proposed, as it advances the theoretical foundation, highlights in the literature the growing production on the subject of e-voting with the use of blockchain technology, proposes a simple architecture that incorporates an auditability character to the e-voting system, performs a performance analysis using the hyperledger platform, providing a more in-depth understanding of the characteristics of this platform, and finally validates the possibility of creating a complete e-voting system using blockchain technology and the hyperledger platform.